1984
DOI: 10.1002/art.1780270718
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA‐Bw35 with mucocutaneous lesions in rheumatoid arthritis patients undergoing sodium aurothiomalate therapy

Abstract: In previous studies, it has been demonstrated that adverse reactions during aurothiomalate therapy for rheumatoid arthritis (RA) might have a genetic basis. Thus, Panayi et al (1) and Wooley et a1 (2) showed that patients who were positive for HLA-B8 and DR3 had a significantly increased risk of developing toxic kidney manifestations during sodium aurothiomalate or D-penicillamine therapy. These studies were confirmed (3) and extended by Bardin et a1 (4) who observed a correlation between gold salt intolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1

Year Published

1985
1985
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…26 The frequency of Dw3 in our patients with proteinuria, however, was markedly lower than that of DR3 reported from England'0 but agreed with the frequencies reported from Norway'2 and from the United States. The comparison of gold induced mucocutaneous lesions with HLA antigens showed a similar trend of increased HLA-B35 and Dwl frequencies as reported by Nuesslein et al,13 although the current differences were not statistically significant. In patients with gold induced interstitial pneumonitis there was also a high prevalence of HLA-Dwl and B35.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…26 The frequency of Dw3 in our patients with proteinuria, however, was markedly lower than that of DR3 reported from England'0 but agreed with the frequencies reported from Norway'2 and from the United States. The comparison of gold induced mucocutaneous lesions with HLA antigens showed a similar trend of increased HLA-B35 and Dwl frequencies as reported by Nuesslein et al,13 although the current differences were not statistically significant. In patients with gold induced interstitial pneumonitis there was also a high prevalence of HLA-Dwl and B35.…”
Section: Discussionsupporting
confidence: 85%
“…For gold induced proteinuria the relative risks were 14 7-fold and 28-2-fold for those with antigens B8 and Dw3 respectively. Nuesslein et al,13 although the current differences were not statistically significant. In patients with gold induced interstitial pneumonitis there was also a high prevalence of HLA-Dwl and B35.…”
Section: Patientscontrasting
confidence: 56%
“…The frequency of DR4 was found to be increased in most RA populations studied,2 and it has been suggested that certain DR antigens, especially DR3, are related to drug toxicity.4 Recently it has also been observed in patients with RA treated with sodium aurothiomalate that class I antigens (B35 and Cw4) are associated with the development of nephritis and dermatitis.5 6 We have previously reported that HLA-DR1 and not DR4 is associated 7 with RA in Israeli patients, as opposed to other Caucasian populations. The type of gold used by us (sodium aurothioglucose) is also different from the preparations studied previously.…”
mentioning
confidence: 99%
“…4 Recently it has also been observed in patients with RA treated with sodium aurothiomalate that class I antigens (B35 and Cw4) are associated with the development of nephritis and dermatitis.5 6 Table 1 summarises the demographic and clinical data of patients with (group A) and without (group B) gold salt toxicity. There were no significant differences between the groups with respect to age, sex, disease duration, and the presence of rheumatoid factor.…”
mentioning
confidence: 99%
“…. k V ---* * * response to gold [10, 14, 15], However, gold-induced proteinuria [9-11, 13, 25-28], thrombocytopenia [8,25] and dermatitis [10,13,27,29] have also been reported to be associated with HLA-DR3. Moreover, sideeffects were reported to occur more frequently in responders compared with non-responders in several studies on gold-treated RA patients [10,14,30].…”
Section: Discussionmentioning
confidence: 99%